ANALISIS PERAN ORANG TUA DALAM MENDUKUNG PROSES BELAJAR DI RUMAH PADA ANAK YANG MENGALAMI KETERLAMBATAN BELAJAR (STUDI KASUS PADA ANAK DI TK NEGERI PEMBINA KUPANG) - Maria Rosalia Valentiani; Kristin Margiani; Nafita Tampubolon, Gokma; Kale, Sartika (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was done to look at how parents help their children with learning delays learn at home, specifically at TK Negeri Pembina Kupang. This study used a descriptive qualitative method and focused on a case study approach. The participants included the parents of two children who have learning delays as the main people providing information, and other family members served as additional informants. Data was gathered by watching, talking to people, and keeping records, then looked at carefully using methods like simplifying the information, showing it clearly, and coming up with final thoughts. The study found that parents have key roles as teachers, encouragers, helpers, guides, and examples in helping their children learn at home. Parents were there with their children during learning activities, gave them encouragement and praise, set up the learning environment, helped them when they had trouble understanding, and showed good behavior in everyday life. However, some challenges were found, like parents not having enough time, kids struggling to stay focused, and them getting bored quickly during learning tasks. So, it's important for parents and teachers to work together well to give better support for kids who have trouble learning. Keywords: parental role, home learning, learning delay, early childhood.